Exploring Turn-Taking Strategies Utilised by Pre-Service Teacher in Indonesian EFL Setting: A Conversation Analysis - Wahid Permana Putra, Rizal; Mira Yusiana, Sifreni; Elfiyanto, Sonny (Journal of Language and Literature Studies, 2024)
In the teaching-learning process, a classroom conversation is managed by the teacher to attain specific purposes. The success of teaching-learning process, in addition, requires teacher-student interaction to gain relevant experiences in students’ target language. During the class, taking-turn will likely happen in a classroom interaction. However, during this class, the teacher-student turn seems to be asymmetrical. The teacher tends to be the main speaker allocating the turn to maintain teacher-student interaction. This research, further, aims at exploring turn-taking strategies utilised by EFL pre-service teacher. The researcher utilises a qualitative research approach with a conversation analysis. The data used in this research is unscripted-recorded classroom video. Furthermore, the data is transcribed into conversational data to obtain the data of turn-taking strategies utilised by pre-service teacher in EFL classroom setting. In analysing the data, the researcher ulitises Sacks’ framework (1984). Based on the result of data analysis, it is found that there are seven turn-taking strategies utilised by pre-service teacher in EFL classroom settting. These are adjacency pairs, addressing term, utterance in-completor, repair technique, possible pre-closing, overlaps, and tag question. In addition, the teacher mostly uses question-answer adjacency pairs during the teaching-learning process. This, however, leads to asymmetric turn between teacher and students. The teacher seems to be more dominant to initiate and take turn during classroom conversation. Possible pre-closing, on the other hand, is the least turn-taking strategy used by the pre-service teacher in the teaching-learning process. This turn used by pre-service teacher to close or end a conversation in the teaching-learning process. Since this research has dealt with pre-service teacher, the results will be beneficial for the pre-service teacher to manage turn-taking strategies in EFL classroom setting to ensure the classroom interaction and conversation symmetrical.